ANALISIS KINERJA BERDASARKAN FAKTOR EKSTERNAL (Studi Kasus pada Pegawai DPMG Kabupaten Pidie Jaya) - Satria, Andi; Ibrahim, Ibrahim (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2025)
The study analyzed external factors of employees in improving their performance. Study on employees of the Community and Village Empowerment Service (DPMG) of Pidie Jaya district. External factors, limited to excess work mutation, workload and interpersonal conflict that occurs in the DPMG Pidie Jaya environment. With a quantitative associative method and research objects of 42 employees. The results found that: (1) Increased employee performance has a positive effect from the implementation of employee work mutations. (2) The effect of workload has a positive impact on employee performance, (3) Interpersonal conflict also has a negative effect on employee performance. 4) Simultaneously, work mutation, workload and interpersonal conflict contribute to changes in employee performance by 52,6%.